تقييم أداء آلة زراعة حافظة محلية الصنع لزراعة العدس ومقارنتها بالزراعة التقليدية بآلة تسطير الحبوب - نور الدين التنبي محمد; سلو منتهى (Latakia University Journal -Biological Sciences Series, 2019)
تقييم أداء آلة زراعة حافظة محلية الصنع لزراعة العدس ومقارنتها بالزراعة التقليدية بآلة تسطير الحبوب محمد نور الدين التنبي منتهى سلو يمثل نظام الزراعة الحافظة مجموعة مفاهيم وممارسات زراعية متفاعلة ومكملة لبعضها البعض، حيث تتم الزراعة بواسطة آلة زراعة (بذارة) آلية تضمن عدم تحريك التربة وبالتالي المحافظة على رطوبتها من خلال ترك بقايا المحاصيل على سطحها والذي بدوره يساهم في تغيير البنية الفيزيائية والكيميائية للتربة. أجري هذا البحث بهدف اختبار آلة زراعة حافظة (زراعة مباشرة دون حرث) محلية الصنع لزراعة محصول العدس ومقارنتها مع الزراعة التقليدية (حراثة بالمحراث الحفار + الزراعة بآلة تسطير الحبوب) من خلال التأثير على كثافة التربة الظاهرية وانضغاط التربة والذي ينعكس على نمو النبات ويظهر في إنتاج المحصول النهائي. أظهرت النتائج أن: - قيم الكثافة الظاهرية باستخدام آلة الزراعة الحافظة على عمق من (10 - 20 سم) أعلى بقليل مما هي عليه باستخدام آلة التسطير (نظام الزراعة التقليدية)، حيث لا توجد فروق معنوية بين المعاملتين. - قيم مقاومة اختراق التربة باستخدام آلة الزراعة الحافظة أعلى بقليل مما هي عليه باستخدام آلة التسطير، ولا يوجد فروق ، وهذا يتوافق مع قيم الكثافة الظاهرية. - انتشار الجذور العرضي والطولي في الزراعة التقليدية (باستخدام آلة التسطير) يتفوق على الزراعة الحافظة (باستخدام آلة الزراعة الحافظة) وبنسبة كبيرة. - هناك فروق بسيطة في الوزن الكلي (حبوب العدس + القش)، وزن حبوب العدس، وكذلك وزن القش، ما بين الزراعة التقليدية باستخدام آلة التسطير والزراعة الحافظة باستخدام آلة الزراعة الحافظة. The conservation agriculture system preserves a set of agricultural concepts and practices that are interactive and complementary to each other, where the cultivation is done by a machine that ensures that the soil is not moved and thus maintains its moisture by leaving the crop residue on its surface which contributes to changing the physical and chemical structure of the soil. This research was carried out with the aim of testing a conservation planter (direct sow without tillage) for planting lentils and comparing it with conventional agriculture (tillage plowing + grain drill) by influencing the bulk density of the soil and soil compression, which is reflected in the growth of the plant and appears in the production of the final crop. The results showed that: - The bulk density of the conservation planter at a depth of (10-20 cm) is slightly higher than that of the grain drill (traditional farming system). There are no significant differences between the two treatments. - The values of soil penetration resistance using the conservation planter is slightly higher than using the grain drill, and there are no significant differences. This corresponds to the density values. - The prevalence of transverse and longitudinal roots in traditional agriculture (using the grain drill) is superior to that of conservation agriculture (using a conservation planter). - There are little significant differences in total weight (lentils + straw), weight of lentils and straw weight, between traditional agriculture using the grain drill and conservation agriculture using the conservation planter.